PARADIGMA MASLAHAH SEBAGAI FONDASI ILMU EKONOMI SYARIAH KONTEMPORER - Heri Sutopo Heri (JSE: Jurnal Sharia Economica, 2026)
The development of contemporary Islamic economics has grown significantly; however, it still faces fundamental challenges related to its epistemological foundation and scientific orientation. The dominance of legal-formal and technical approaches in both academic discourse and practical implementation often leads to the marginalization of substantive welfare objectives, which constitute the core purpose of Islamic law. This study aims to analyze the concept of maslahah as a paradigmatic foundation for contemporary Islamic economics. Employing a qualitative approach with a library research method, this study critically examines classical and contemporary literature derived from authoritative books, accredited national journals, and reputable international journals. The findings indicate that maslahah holds strong potential as a paradigm for Islamic economics, as it shapes foundational assumptions, scientific objectives, and methodological orientations grounded in collective welfare, social justice, and sustainability. Nevertheless, existing studies tend to position maslahah merely as a normative or limited applicative principle rather than as a comprehensive epistemological framework. This study underscores the urgency of reconstructing Islamic economics based on the maslahah paradigm to address contemporary economic challenges in a more holistic and equitable manner